2002
DOI: 10.13181/mji.v11i4.79
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence level in children with cerebral palsy (CP) at YPAC Medan

Abstract: Abstrak Anak cerebral palsy memiliki masalah kesulitan makan yang menyebabkan asupan zat gizinya kurang, sehingga peran pengasuh sangatlah penting. Posisi pemberian makan adalah salah satu cara untuk mengatasi masalah makan pada anak cerebral palsy. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan pengasuh tentang posisi pemberian makan dengan asupan energi dan protein pada anak cerebral palsy di Yayasan Pembinaan Anak Cacat (YPAC) Malang. Desain penelitian ini adalah cross sectional study. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, it is generally believed that gender has no role on the development of cerebral palsy. Rambe et al 8 of mixed type of cerebral palsy in severe mental X2=5.957; df = 3; P = 0.114 retardation. Our results were in line with Hutton and which stated prevalence of cerebral palsy children who suffered from mental retardation damage location inside the brain and types of cerebral palsy which also determine the type.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it is generally believed that gender has no role on the development of cerebral palsy. Rambe et al 8 of mixed type of cerebral palsy in severe mental X2=5.957; df = 3; P = 0.114 retardation. Our results were in line with Hutton and which stated prevalence of cerebral palsy children who suffered from mental retardation damage location inside the brain and types of cerebral palsy which also determine the type.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, Rambe et al 8 showed a definite association between types of cerebral palsy and congnitive level, but on the other hand other investigators found that such association does not exist.…”
mentioning
confidence: 94%